NILAI INDEKS GLIKEMIK BEBERAPA JENIS PENGOLAHAN JAGUNG MANIS (Zea mays saccharata Sturt) - Sri Nur Amalia; Rimbawan Rimbawan; Mira Dewi (Jurnal Gizi dan Pangan, 2011)
The implementation of glycemic index can be used as basis for selecting carbohydrate food source to enhance and or to maintain health.The objective the following study was to analyze the glycemic indices of sweet corn with three different cooking methods.  Glycemic index values of boiled, sauted and grilled sweet corn were 41.22, 31.08 and 55.31 respectively. Based on those results, grilled sweet corn was classified as food with medium glycemic index, whereas both of boiled and sauted sweet corn were classified as food with low glycemic index.